How can gamification contribute to achieve SDGs? : Exploring the opportunities and challenges of ecogamification for tourism - Souza, Viviane Silva (2021)
Purpose Ecogamification can make a positive impact on Tourism. With this in mind, the present study aims to examine specific stakeholders – those positioned at the upstream side of gamification process – and their perspectives concerning not only the benefits, but also the challenges of (eco)gamification. Design/methodology/approach The study follows a qualitative-exploratory approach and bases its results on the analysis of 10 in-depth interviews conducted with buyers and providers from the emerging Portuguese tourism and tech markets. Findings Results shed light on key benefits of ecogamification, including its potential to promote “green” behaviour, transmit complex information through entertainment, reward users for good practices, improve engagement and help avoiding overtourism. Simultaneously, there are important challenges to overcome, including the lack of investment, resistance to new technologies, low eco-consciousness of tourists and distraction from issues that matter. Further, findings show that ecogamification takes on different and specific roles for buyers and providers. Research limitations/implications The research limitations are mainly related to the sample size. Practical implications An effective ecogamification process depends on the integration of the supply and demand sides and, at the same time, on the responsibility of different stakeholders (providers, buyers, players) across the value chain, through a broad logic of B2B2C. Originality/value This study contributes towards a better understanding of ecogamification in tourism, through the eyes of buyers and providers and also provides insights regarding the role of these specific stakeholders and the relationship between them.